Bromus cincinnatus (Poaceae): perennial oat-grass or annual brome-grass? - Romero Zarco, Carlos (Mediterranean Botany, 2023)
A former lectotype for Bromus cincinnatus Ten. (Poaceae) has been superseded, as it is in serious conflict with the protologue. Another element of the protologue has been designated as the effective lectotype. The new lectotype is identified as coespecific with Bromus intermedius Guss., a Mediterranean species of Bromus L. subg. Bromus. The new combination Helictochloa panormitana (Lojac.) Romero Zarco is proposed for the species originally described as Avena australis Parl., nom. illeg., which is currently known as Helictochloa cincinnata auct. The lectotypes of Avena panormitana Lojac., Avena opulenta Lojac., and Bromus intermedius Guss. are also designated.